Indonesia Insurance Development with Various Aspects and Prespectives of The Regulatory Approach - Sopian, Arip; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2023)
The study focused on the development of insurance in Indonesia from time to time, with a review of its definitions and uses, which can be interpreted as an agreement in which the insurer binds himself to the insured by receiving a premium, to compensate for losses, or not to obtain the expected benefits, which can be borne due to events which is not known in advance. In order to get insurance coverage for risks that may occur, the insured must pay a premium to the insurance company within a certain period of time. Insurance in general means security, compensation, guarantee, protection. Insurance is a transfer of risk by paying premiums or fees (a certain amount) with a guarantee to get compensation in the form of benefits or packages (compensation) in the event of a certain loss (special loss) due to a risk (including the risk of illness). There are two essential elements in insurance, namely risk transfer and loss sharing. Insurance from an economic point of view is a method of reducing risk by moving and combining protection against financial losses. From another point of view, a business for example, is a company whose main business is receiving or selling services, transferring risks from other parties, and obtaining profits by sharing risks among a number of its customers. This study uses a literature review which is part of a qualitative study, which is related to the subject of insurance research in Indonesia.